Current trends and insights on EMS mutagenesis application to studies on plant abiotic stress tolerance and development - Chen, Liuzhu; Duan, Liu; Sun, Minghui; Yang, Zhuo; Li, Hongyu; Hu, Keming; Yang, Hong; Liu, Li (Frontiers in Plant Science, 2023)
Ethyl methane sulfonate (EMS)-induced mutagenesis is a powerful tool to generate genetic resource for identifying untapped genes and characterizing the function of genes to understand the molecular basis of important agronomic traits. This review focuses on application of contemporary EMS mutagenesis in the field of plant development and abiotic stress tolerance research, with particular focuses on reviewing the mutation types, mutagenesis site, mutagen concentration, mutagenesis duration, the identification and characterization of mutations responsible for altered stress tolerance responses. The application of EMS mutation breeding combined with genetic engineering in the future plant breeding and fundamental research was also discussed. The collective information in this review will provide good insight on how EMS mutagenesis is efficiently applied to improve abiotic stress tolerance tolerance of crops with the utilization of Next-generation sequencing (NGS) for mutation identification.